Peer review of the pesticide risk assessment of the active substance aluminium silicate calcined (kaolin calcined). (17th November 2022) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Greece and co‐rapporteur Member State France for the pesticide active substance aluminium silicate calcined (kaolin calcined) and the considerations as regards the Article 12 MRL review of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of aluminium silicate calcined (kaolin calcined) as an insect repellent via broadcast spray application on grapevine, apricot tree, almond tree, cherry tree, hazel tree, walnut tree, peach tree, apple tree, pear tree, quince tree, nashi tree, plum tree, citrus tree, lavender, lavandin and olive tree, as proposed by the applicants. The reliable endpoints, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.